Protection from Inflammatory Organ Damage in a Murine Model of Hemophagocytic Lymphohistiocytosis Using Treatment with IL-18 Binding Protein - Chiossone, Laura; Audonnet, Sandra; Chetaille, Bruno; Chasson, Lionel; Farnarier, Catherine; Berda-Haddad, Yael; Jordan, Stefan; Koszinowski, Ulrich; Dalod, Marc; Mazodier, Karin; Novick, Daniela; Dinarello, Charles; et al. (Frontiers in Immunology, 2012)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition due to the association of an infectious agent with lymphocyte cytotoxicity defects, either of congenital genetic origin in children or presumably acquired in adults. In HLH patients, an excess of lymphocyte or macrophage cytokines, such as IFN-γ and TNFα is present in serum. In animal models of the disease, IFN-γ and TNF-α have been shown to play a central pathogenic role. In humans, unusually high concentrations of IL-18, an inducer of IFN-γ and TNF-α have been reported, and are associated with an imbalance between IL-18 and its natural inhibitor IL-18 binding protein (IL-18BP) resulting in an excess of free IL-18. Here we studied whether IL-18BP could reduce disease severity in an animal model of HLH. Mouse cytomegalovirus infection in perforin-1 knock-out mice induced a lethal condition similar to human HLH characterized by cytopenia with marked inflammatory lesions in the liver and spleen as well as the presence of hemophagocytosis in bone marrow. IL-18BP treatment decreased hemophagocytosis and reversed liver as well as spleen damage. IL-18BP treatment also reduced both IFN-γ and TNF-α production by CD8+ T and NK cells, as well as Fas ligand expression on NK cell surface. These data suggest that IL-18BP is beneficial in an animal model of HLH and in combination with anti-infectious therapy may be a promising strategy to treat HLH patients.